Inhibitory Motor Control in Old Age: Evidence for De-Automatization? - Maylor, Elizabeth A.; Birak, Kulbir S.; Schlaghecken, Friederike (Frontiers in Psychology, 2011)
To examine age-related effects on high-level consciously-controlled and low-level automatically-controlled inhibitory processes, the Simon task was combined with the masked prime task in a hybrid procedure. Young and older adults responded to the identity of targets (left/right key-press to left-/right-pointing arrows) that appeared on the left/right of the screen and were preceded by left-/right-pointing backward-masked arrow primes at fixation. Responses were faster and more accurate when the target was congruent with its location than incongruent (Simon effect), and when the target was incompatible with the prime than compatible (negative compatibility effect; NCE). The Simon effect was disproportionately larger, and the NCE disproportionately delayed, in older adults compared to young adults, indicating both high- and low-level inhibitory control deficits with aging. Moreover, the two effects were additive in young adults, but interactive in older adults, providing support for the dedifferentiation hypothesis of aging. Specifically, older adults’ prime-related inhibitory control appeared improved on incongruent relative to congruent trials, suggesting that impaired automatic control was substituted by high-level, non-automatic processes.